Blockchain Strategy in Improving Transaction Security in The Sharia Capital Market - Ibnu Habib Wahyudi; Imsar; Harahap, Muhammad Ikhsan (Jurnal Manajemen Bisnis, 2024)
This study aims to investigate the strategy of blockchain technology in improving transaction security in the shariah capital market. Using an in-depth interview approach, this research explores the perceptions and understandings of various stakeholders, including industry experts, regulators, and shariah capital market practitioners. Qualitative research methods were used to gain in-depth insights into how blockchain can be applied to strengthen transaction security in the shariah capital market. From the research results, it is concluded that blockchain technology has tremendous potential and relevance in improving transaction security in the Islamic capital market, in this case the use of smart contracts makes a considerable contribution, in its implementation smart contracts can increase security, transparency and efficiency, In the context of the shariah capital market, the principle of "sharia can run automatically without third party intermediaries, this is very possible through smart contracts, not only that, the decentralized nature of the blockchain makes it very difficult to hack, and quite a lot of obstacles are passed to be able to hack it, and make a significant contribution to increasing transactions and security in the shariah capital market.